Changes in gut bacterial communities and the incidence of antibiotic resistance genes during degradation of antibiotics by black soldier fly larvae - Liu, Cuncheng; Yao, Huaiying; Chapman, Stephen J.; Su, Jianqiang; Wang, Cunwen (Environment international, 2020)
[Display omitted] •Oxytetracycline can be degraded effectively by black soldier fly larvae.•Intestinal microorganisms facilitate the bioremediation of antibiotic contamination.•This is the first report of ARGs and MGEs in the gut of black soldier fly larvae. As a saprophytic insect, the black soldier fly can digest organic waste efficiently in an environmentally friendly way. However, the ability and efficiency of this insect, and the microbial mechanisms involved, in the degradation of antibiotics are largely uncharacterized. To obtain further details during the degradation of OTC (oxytetracycline) by black soldier fly larvae (larvae), the changes in intestinal bacterial communities were examined. Both ARGs (antibiotic resistance genes) and MGEs (mobile genetic elements) were found within the larval guts. At the end of the degradation period, 82.7%, 77.6% and 69.3% of OTC was degraded by larvae when the initial concentrations were 100, 1000 and 2000 mg kg−1 (dry weight), respectively, which was much higher than the degradation efficiencies (19.3–22.2%) without larvae. There was no obvious effect of OTC on the development of the larvae. Although the larval gut microorganisms were affected by OTC, they adapted to the altered environment. Enterococcus, Ignatzschineria, Providencia, Morganella, Paenalcaligenes and Actinomyces in the gut responded strongly to antibiotic exposure. Interestingly, numerous ARGs (specifically, 180 ARGs and 10 MGEs) were discovered, and significantly correlated with those of both integron-integrase gene and transposases in the larval gut. Of all the detected ARGs, tetracycline resistance genes expressed at relatively high levels and accounted for up to 67% of the total ARGs. In particular, Enterococcus, Ignatzschineria, Bordetella, Providencia and Proteus were all hosts of enzymatic modification genes of tetracycline in the guts that enabled effective degradation of OTC. These findings demonstrate that OTC can be degraded effectively and prove that the bioremediation of antibiotic contamination is enhanced by larvae. In addition, the abundance of ARGs and MGEs formed should receive attention and be considered in environmental health risk assessment systems.